Gender Differences in Negotiation: Evidence from Real Estate Transactions. Issue 636 (17th February 2021) - Andersen, Steffen; Marx, Julie; Nielsen, Kasper Meisner; Vesterlund, Lise
Abstract: Negotiations over real estate show that men secure better prices than women. However, gender differences decrease when improving controls for the property's value; and is eliminated when controlling for unobserved heterogeneity in a repeated-sales sample. Rather than evidence of differences in negotiation, price differences result from men and women demanding different properties. Consistently we find no gender difference in sales prices secured for inherited property. Provided appropriate controls men and women fare equally well when negotiating over real estate. Our study demonstrates that inference on gender differences in negotiation relies critically on controlling for the value of the negotiated item.